Politik Antariksa: Proses dan Dinamika Politik di Balik Kegiatan Keantariksaan di Indonesia - M. Bashroni Shidqon (Universitas Airlangga, 2023)
The Unitary State of The Republic of Indonesia is a state which requires a mastery of space technology to be able to fulfill various needs and achieve national interests. Besides, it will increase the bargaining power of the state in the international political constellation. The study was aimed to the discussion of the processes, dynamics, and obstacles to the implementation of Indonesian space namely the limited willingness or political support that has an impact on the limited budget allocation for space activities, which encourages the actors behind Indonesian space activities who have motivation or interests, undertake various efforts to carry out activities space in Indonesia in order to gain political support in making policy decisions and budget allocations needed to achieve predetermined targets.